A fully self‐powered, natural‐light‐enabled fiber‐optic vibration sensing solution. Issue 4 (7th November 2021) - Wang, Jiaqi; Man, Ho‐Yin; Meng, Cuiling; Liu, Pengcheng; Li, Shaoxin; Kwok, Hoi‐Sing; Zi, Yunlong
Abstract: Fiber‐optic sensors have been developed to monitor the structural vibration with advantages of high sensitivity, immunity to electromagnetic interference (EMI), flexibility, and capability to achieve multiplexed or distributed sensing. However, the current fiber‐optic sensors require precisely polarized coherent lasers as the lighting sources, which are expensive in cost and suffer from the power supply issues while operating at outdoor environments. This work aims at solving these issues, through developing a fully self‐powered, natural‐light‐enabled approach. To achieve that, a spring oscillator‐based triboelectric nanogenerator (TENG), a polymer network liquid crystal (PNLC), and an optical fiber were integrated. The external vibration drove the PNLC to switch its transparency, allowing the variation of the incident natural light in the optical fiber. Compared with the majority of conventional TENG‐based active vibration sensors, the developed paradigm does not suffer from the EMI, without requirements of the signal preamplification which consumes additional energy. The vibration displacement monitoring was performed to validate the sensing effectiveness of the developed paradigm. Abstract : Through the combination of a triboelectric nanogenerator (TENG), a polymer network liquid crystal (PNLC) and an optical fiber, a fully self‐powered, sunlight modulation‐based structural vibration sensing system was successfully developed without the impact of electromagnetic interference (EMI) and the demands of signal preamplification. Ubiquitous natural light, rather than the expensive, well polarized, and preciously collimated laser light, was utilized for the lighting source for the optical fiber sensing, serving as the information carrier.